Surge of Typhoid Intestinal Perforations as Possible Result of COVID-19–Associated Delays in Seeking Care, Madagascar - Hyon Jin Jeon (Centers for Disease Control and Prevention, 2021)
During the coronavirus disease pandemic, we observed a 6.4-fold increase in typhoid intestinal perforation incidence in Antananarivo, Madagascar. Thirteen perforations occurred within 6 months (February 2020–July 2020), compared with 13 perforations during the previous 41 months (August 2016–January 2020). The increase may be attributable to delayed healthcare seeking during the pandemic.